A void and a challenge: Rules of engagement at sea in a low-intensity conflict environment. (2nd July 2016) - Khurana, Gurpreet S.
ABSTRACT: The armed forces are usually conversant with the rules on the use of force against the enemy in the traditional battle space. However, military forces are usually ill-equipped for this when the opponent is not a regular combatant but an un-uniformed person – a militant or even a criminal – operating in seemingly benign environs. This constitutes a serious legal void, particularly given the emerging environment wherein navies would be increasingly tasked to perform non-traditional constabulary functions. The trend is best exemplified by the case of the Indian Navy that was entrusted with the responsibility for the nation's overall maritime security, including coastal and offshore security. This paper examines the concept and the salient issues relating to rules of engagement (RoE) for maritime forces operating in the low-intensity conflict environment.